2022
DOI: 10.3389/fmicb.2022.831888
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of phoD- and gcd-Harboring Microbial Communities Across an Age Sequence of Biological Soil Crusts Under Sand-Fixation Plantation

Abstract: Biological soil crusts (BSCs) are important for restoring vegetation and improving soil fertility in arid or semiarid desertified land. However, studies on the contribution of BSC microbes to phosphorus (P) transformation remains limited. The microbial diversity involved in P transformation and its dynamic along BSC development should be examined to further understand the microbial regulatory mechanism of the P-cycling process. This paper investigates the soil properties, P fractions, and potential of P transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Soil P was also increased under BSCs ( Figure 1 ). Studies have shown that with the development of BSCs, soil microbial abundance can be improved [ 40 ]. Soil microorganisms are the determinant of P speciation and the key driver of P transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Soil P was also increased under BSCs ( Figure 1 ). Studies have shown that with the development of BSCs, soil microbial abundance can be improved [ 40 ]. Soil microorganisms are the determinant of P speciation and the key driver of P transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The Planctomycetaceae includes major bacteria in global N and C cycles ( Strous et al, 1999 ). In addition, the Planctomycetaceae are also typical phosphate-solubilizing bacteria, which contain phoD or phoC genes ( Zhao et al, 2022 ). Therefore, the Planctomycetaceae have important roles in biogeochemical cycles.…”
Section: Discussionmentioning
confidence: 99%